2005
DOI: 10.1111/j.0001-6349.2005.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of transforming growth factor‐α, epidermal growth factor, and vascular endothelial growth factor expression in hyperstimulated rat ovary

Abstract: TGF-alpha, EGF, and VEGF are found to have increased in the hyperstimulated ovaries and this finding seems to be involved in the OHSS pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Regulation of the VEGF system seems to be important for controlling ovarian hyperstimulation (29). Previously, enhanced expression of VEGF proteins in the stroma, endothelium, and granulosa cells has been shown in hyperstimulated ovaries (30). In vitro, VEGF expression was confirmed in human granulosa cells and could be induced in response to administration of hCG (14,31).…”
Section: Discussionmentioning
confidence: 96%
“…Regulation of the VEGF system seems to be important for controlling ovarian hyperstimulation (29). Previously, enhanced expression of VEGF proteins in the stroma, endothelium, and granulosa cells has been shown in hyperstimulated ovaries (30). In vitro, VEGF expression was confirmed in human granulosa cells and could be induced in response to administration of hCG (14,31).…”
Section: Discussionmentioning
confidence: 96%
“…In vitro studies confirmed that TGF-α, which was localized and expressed at ovarian follicles and stroma interval, has a regulatory role on ovarian tissue during entire procedure of growth, degeneration, and atresia of follicular. [ 27 , 28 ] TGF-α was highly expressed in oocytes during primordial follicles stage, then the expression of TGF-α gradually decreases along with maturation of follicles, which implies that TGF-α synthesized in early stage of follicle formation might participates in development of primordial follicles and early growth of oocytes. [ 29 , 30 ] Thalidomide not only plays an immune-inhibitory role for TNF-α, interleukin 6 (IL-6), and interleukin 8 (IL-8) but also an inhibitory role for TGF-α and TGF-β.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NO-induced vasodilation, there is VEGFinduced angiogenesis in the preovulatory follicle in the hours preceding ovulation (26). Granulosa cells do produce VEGF (27), and VEGF from follicular fluid and granulosa cells induces vessel growth in the ovary (28).…”
Section: Discussionmentioning
confidence: 99%